Implications of the Hybrid Epithelial/Mesenchymal Phenotype in Metastasis - Jolly, Mohit Kumar; Boareto, Marcelo; Huang, Bin; Jia, Dongya; Lu, Mingyang; Ben-Jacob, Eshel; Onuchic, José N.; Levine, Herbert (Frontiers in Oncology, 2015)
Understanding cell-fate decisions during tumorigenesis and metastasis is a major challenge in modern cancer biology. One canonical cell-fate decision that cancer cells undergo is Epithelial-to-Mesenchymal Transition (EMT) and its reverse Mesenchymal-to-Epithelial Transition (MET). While transitioning between these two phenotypes – epithelial and mesenchymal, cells can also attain a hybrid epithelial/ mesenchymal (i.e. partial or intermediate EMT) phenotype. Cells in this phenotype have mixed epithelial (eg. adhesion) and mesenchymal (eg. migration) properties, thereby allowing them to move collectively as clusters of Circulating Tumor Cells (CTCs). If these clusters enter the circulation, they can be more apoptosis-resistant and more capable of initiating metastatic lesions than cancer cells moving individually with wholly mesenchymal phenotypes, having undergone a complete EMT. Here, we review the operating principles of the core regulatory network for EMT/MET that acts as a ‘three-way’ switch giving rise to three distinct phenotypes – epithelial, mesenchymal and hybrid epithelial/mesenchymal. We further characterize this hybrid E/M phenotype in terms of its capabilities in terms of collective cell migration, tumor-initiation, cell-cell communication, and drug resistance. We elucidate how the highly interconnected coupling between these modules coordinates cell-fate decisions among a population of cancer cells in the dynamic tumor, hence facilitating tumor-stroma interactions, formation of CTC clusters, and consequently cancer metastasis. Finally, we discuss the multiple advantages that the hybrid epithelial/mesenchymal phenotype have as compared to a complete EMT phenotype and argue that these collectively migrating cells are the primary ‘bad actors’ of metastasis.